A systematic approach to assess mine atmospheric status - Cheng, Jianwei; Zhou, F. (2013)
Methane and coal dust explosions are the most feared hazards in the coal industry worldwide. The large majority of these explosions originates from or occurs around sealed mine areas. On the other hand, nearly all coal mine explosions initially start with the ignition of combustible gases such as methane, carbon monoxide, etc. Technically speaking, the explosibility of a mine atmosphere depends on the composition of oxygen, combustibles and inert gases. However, the compositions in an inaccessible sealed mine areas change with time under the influences of inflows of combustible gases, air leakage, inert gases injected, etc. In order to improve mine safety, it is desirable to have a tool to accurately simulate the gas compositions in a sealed area and to determine its explosibility. In this paper, a mathematical model to simulate atmospheric compositions in a sealed mine volume is developed, and the original Coward explosive triangle method is expanded for determining the explosibility. Finally, a case study is used to show the applicability of the developed model and the explosibility changes over time are also plotted with the help of the expanded Coward method. In addition, the USBM explosibility diagram is used to verify the results derived by the expanded Coward method. © 2013 Elsevier Ltd.